Babe & me : a baseball card adventure - Gutman, Dan (Gutman, Dan. Baseball card adventures., 2002)
With their ability to travel through time using vintage baseball cards, Joe and his father have the opportunity to find out whether Babe Ruth really did call his shot when he hit that homerun in the third game of the 1932 World Series against the Chicago Cubs.